Zr-doped phosphorus-containing activating carbons catalysts for the valorization of furfural into valuables products in one-pot reaction - Maderuelo-Solera, Rocío; García-Mateos, Francisco José; Rodríguez Carballo, Gabriela; García-Sancho, Cristina; Rosas-Martínez, Juana María; Moreno-Tost, Ramón; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás; Maireles-Torres, Pedro Jesús; Cecilia-Buenestado, Juan Antonio (Elsevier, 2025)
Olive stones have been used to synthesize activated carbon using H3PO4 as activating agent under pyrolytic treatment. Then, Zr species have been incorporated by impregnation and subsequent calcination, obtaining acid catalysts with Lewis and Brønsted sites, which are involved in the one-pot reaction of furfural in value-added products. All catalysts display a high micro- and mesoporosity. The catalysts showed different behavior as a function of the temperature, obtaining full conversion after 24 hours at 110 ºC, being mainly selective towards furfuryl alcohol and i-propyl furfuryl ether. The study at higher temperature (170 ºC) reached the full conversion after only 45 minutes, being preferentially selective towards i-propyl levulinate and γ-valerolactone. The catalysts are prone to suffer deactivation processes due to the formation of humins on the surface of the catalysts, which cause a decrease of the available active sites.
Keywords: Carbón activado; Aldheídos; Furfural; One-pot reaction; Activated carbon; Lewis/Brönsted acid sites